Multifunctional supercapacitor integrated sensor from Oyster and Cicada derived bio-ternary composite: Vanillin/caffeine detections in beverages. (January 2022) - Selvam, Samayanan; Yim, Jin-Heong
Highlights: Supercapacitor combined sensor fabricated from Bio-material composites. Bio-materials chitin isolated from oyster shell and cicada exoskeleton. Chitin/PPy/WS2 composite exhibits good specific capacitance. Caffeine and vanillin detection test reveal good performance. The integrated devices importance for smart electronic and health care devices. Abstract: This study focused bio-materials composite mediated supercapacitor integrated vanillin and caffeine sensor system. The biomaterials isolated from Oyster shell and Cicada exoskeletons. The isolated chitins are functionalized with Tungsten disulfide/Polypyrrole (WS2 /PPy) composite via one-step hydrothermal technique. The elemental, structural, and morphological analyses are conducted with FTIR, XRD, XPS, SEM and TEM. The XPS spectra are exhibit important peaks of S2p, W3d, N1s and C1s. The Oyster chitin/polypyrrole/WS2 composite supercapacitor-sensor electrode archives a specific capacitance of 381.5 Fg −1 and sensitivity for vanillin and caffeine are 0.021 μA μg −1  mL cm −2 and 0.014 μA μg −1  mL cm −2 . The Cicada-chitin/PPy/WS2 composite delivers 311.3 Fg −1 of specific capacitance with sensitivity of vanillin is 0.013 μA μg −1  mL cm −2 and caffeine is 0.01 μA μg −1  mL cm −2 . Cycling tests show good capacitance retention of 90% up to 100, 000 cycles. The performances of bio-mass supercapacitor combined vanillin/caffeine sensor system tested in food and beverage samples. This system provides a feasible route for potentially applicable status in smart electronic devices in the food and beverage industries. Graphical abstract: Image, graphical abstract